The Calcaneal Scarf Osteotomy: Surgical Correction of the Adult Acquired Flatfoot Deformity and Radiographic Results. Issue 5 (October 2013) - Feuerstein, Catherine A.; Weil, Lowell; Weil, Lowell Scott; Klein, Erin E.; Agerakis, Nicholas G.; Akram, Usman
Purpose . Surgical correction of the adult acquired flatfoot deformity (AAFD) is continually evolving. This technique article presents the technique of the calcaneal scarf osteotomy (CSO) and radiographic evidence supporting the ability of this procedure to correct an AAFD. Method . The technique described here is a single osteotomy that corrects flatfoot deformity in all 3 planes. Retrospectively, medical records were reviewed to identify patients who underwent a CSO for surgical correction of AAFD. Pre- and postoperative radiographs were reviewed. Results . Thirty patients (32 feet) had an average age of 49.0 ± 17.2 years (range = 35-73 years) with an average of 5.7 ± 2.0 years (range = 1-11 years) of follow-up. Anteroposterior and lateral radiographic parameters were significantly altered with this procedure (P < .001). CSO-induced calcaneal–cuboid joint arthritis did not occur. Discussion and Conclusions . The results of the current study demonstrate that the CSO significantly changes radiographic exam parameters in patients who suffer from AAFD. Therefore, the CSO provides triplanar correction through one osteotomy with early return to weight bearing and lacks the complications such as lateral column pain associated with other calcaneal osteotomies. Levels of Evidence: Level IV, Retrospective cohort study